2020
DOI: 10.3390/ani10040628
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptome Analysis of Gill Tissue in Response to Hypoxia in Silver Sillago (Sillago sihama)

Abstract: Simple Summary: Silver sillago (Sillago sihama) is a marine fish species with a high economic value. S. sihama is poorly resistant to hypoxia. However, hypoxia stress-related genes and pathways in S. sihama remain unclear. In this study, we compared gill tissues of S. sihama between hypoxia and normoxia groups and detected differentially expressed genes under hypoxia stress. Two gene families, such as cytochrome P450 and glutathione S-transferase were associated with the function of metabolic process under the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 62 publications
0
17
1
Order By: Relevance
“…In all treatment groups, the number of DRGs was higher than that of URGs. A comparative transcriptome analysis of the response of sillago gill tissue to hypoxia indicated that the number of URGs was greater than that of DRGs in different hypoxic treatment groups (Saetan et al, 2020). The number of URGs increased with increasing hypoxic stress duration, contrary to the results of this study.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In all treatment groups, the number of DRGs was higher than that of URGs. A comparative transcriptome analysis of the response of sillago gill tissue to hypoxia indicated that the number of URGs was greater than that of DRGs in different hypoxic treatment groups (Saetan et al, 2020). The number of URGs increased with increasing hypoxic stress duration, contrary to the results of this study.…”
Section: Discussioncontrasting
confidence: 99%
“…In a study of silver sillago (Sillago sihama) under hypoxic stress, transcriptome sequencing technology was used to explore the different expression patterns. Many genes related to steroid and amino acid biosynthesis have been reported (Saetan et al, 2020). A comparative transcriptome analysis showed that the Gymnocypris ecklon reduces energy consumption in response to hypoxic stress by inhibiting cell growth and proliferation (Qi et al, 2018), and mRNA sequencing of large yellow croaker liver tissue showed that carbohydrate metabolism plays a crucial role in energy supply and amino acid metabolism is an important supplement to cope with energy supply (Ding et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…2020 ), transcriptome ( Tian et al. 2019 ; Saetan et al. 2020 ), and draft genomic survey data ( Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…In fish, it potentially was responsible for the lethality of zebrafish VitE-deficient embryos [ 56 ]. It might be activated by low temperature (Nile tilapia), hypoxia (Silver sillago) stress and heavy metal (Japanese flounder) [ 57 59 ], and could be induced by Escherichia coli and then led to the red blood cells (RBCs) death of grass carp [ 60 ]. It could be checked at the gene expression level and characterized by the morphology of mitochondria [ 32 , 35 , 36 , 38 , 39 , 41 45 , 61 ].…”
Section: Discussionmentioning
confidence: 99%